Current Perspectives in Human Papillomavirus 2019
DOI: 10.5772/intechopen.80706
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection and Lung Cancer

Abstract: Lung cancer continues to be the most common neoplasia and represents the leading cause of cancer-related death in the world. Nonetheless, contrary to expected projections, the decrease in incidence expected by decrease in tobacco exposure has been partially halted due to an increasing amount of lung cancer cases in nonsmokers, particularly in female patients. This led to the development of new hypotheses in terms of lung cancer etiology, including the involvement of oncogenic viruses such as the human papillom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…The reason for more frequent HPV infection in LA with EGFR gene mutations could be the viral protein E6. This protein upstream regulates the inhibitors of apoptosis of the EGFR/ PI3K/AKT signaling pathway and may play a central role in NSCLC cancer tumorigenesis with EGFR gene mutations and HPV infection (40,41). Previous studies have confirmed HPV as part of the etiology of cervical and oropharyngeal cancer, but the association with lung cancer has not been fully established (12,25).…”
Section: Meta-analysis Of Hpv Prevalence In Nsclcmentioning
confidence: 99%
“…The reason for more frequent HPV infection in LA with EGFR gene mutations could be the viral protein E6. This protein upstream regulates the inhibitors of apoptosis of the EGFR/ PI3K/AKT signaling pathway and may play a central role in NSCLC cancer tumorigenesis with EGFR gene mutations and HPV infection (40,41). Previous studies have confirmed HPV as part of the etiology of cervical and oropharyngeal cancer, but the association with lung cancer has not been fully established (12,25).…”
Section: Meta-analysis Of Hpv Prevalence In Nsclcmentioning
confidence: 99%
“…The results would suggest that genetics plays an important role in the disparities observed, and this in turn could be further explored to better understand cancer development and even suggest novel therapeutic targets. 27 Other achievements by CLICaP include the characterization of lung cancer in young patients, 28 treatment outcomes in Hispanic patients and potential biomarkers for response, 29,30 mechanisms of resistance to treatment with first-generation tyrosine kinase inhibitors, 31 molecular epidemiology of ALK rearrangements, 32 EGFR exon 20 insertions, 33 EGFR amplifications, 34 KRAS mutations, 35 patterns of progression to treatment with tyrosine kinase inhibitors, 36 outcomes of immunotherapy in Hispanic individuals, 37 characteristics of small cell lung cancer, 38 mesothelioma, 39 thymomas, 40 squamous cell carcinoma, 41 and real-world data from Hispanic individuals treated with novel agents. 42 Furthermore, CLICaP started a mentoring program that seeks to offer effective networking and mentoring opportunities for talented oncologists and investigators from Latin America to promote leadership and address current limitations within the regional setting.…”
Section: Cooperative Groups and The Search For Multidisciplinary Appr...mentioning
confidence: 99%
“…However, other types of tumors have been associated with the activity of HPV [1,2]. One of these possible HPVrelated cancers is lung cancer; however, the presence and activity of the virus remain controversial [3][4][5].…”
Section: Introductionmentioning
confidence: 99%